Implementation of a Notion-Based Manufacturing Information System for Operational Optimization (Case Study of MSMEs Dasteran Bendino) - Yunita Kusumaningrum; Alfina Fauziarahmani; Tiara Ayu Wardani; Diana Fitriyani Putri; Amelia Eka Diyanti; Mutia Elsa Rahayu; Risya Najwa Irawan; Nazlia Alifah; Zidni Ali (Takaza Innovatix Labs Ltd., 2026)
This study examines the integration of Manufacturing Information System (MIS) to improve operational efficiency, inventory control, and readiness at scale for Dasteran Bendino MSMEs. The qualitative descriptive research uses interviews, field observation, and literature review. The results show hybrid operations, manual transaction recording and flow, dependence on suppliers, and centralized administrative burdens; therefore, the addition of divisions (administration, warehousing, logistics, R&D) and the implementation of an integrated digital system (e.g., Notion), along with improvements in transaction flow, automated recording, and supplier diversification, are necessary. The recommended implementation is expected to enhance recording accuracy and the competitiveness of MSMEs in the e-commerce ecosystem.